Financial constraints and investment decisions of listed Indian manufacturing firms - Sanjeev Kumar; K. S. Ranjani (Financial Innovation, 2018)
Background: The purpose of the study is to understand the role of cash flow sensitivity to investment as a measure of financial constraints among listed Indian manufacturing firms. It also analyses the role of tangibility in alleviating financial constraints. Further, the role of other financial factors in investment decisions is explored. Methods: The study is conducted using the generalized method of moments (GMM) estimator on dynamic panel data for the period of (2009-2015) on 768 listed manufacturing firms. Results: The analysis finds that cash flow sensitivity is a valid measure of financial constraints in the Indian manufacturing sector. Results according to splitting criteria found that investment decisions of standalone firms are more sensitive to cash flow than group affiliated firms. Further, splitting the firms according to market capitalization and tangible net worth reveals a higher degree of cash flow sensitivity by firms with lower market capitalization and asset tangibility. The results for the effects of tangibility of assets on easing financial constraint were found significant only in the case of firms with low tangible net worth and medium market capitalization. Conclusions: The study confirms cash flow sensitivity to investment as a valid measure of financial constraints. It will confirm pooling of internal funds by financially constrained firms to accept profitable investment opportunities in future. Further, it also reports that asset tangibility eases the financial constraints faced by firms.
Keywords: 650; Financial constraints; Investment determinants; Market capitalization; Tangible net worth; India; Generalized method of moments